Good Times Are Drinking Times: Empirical Evidence on Business Cycles an Alcohol Sales in Sweden 1861-2000 - Niclas A. Krüger; Mikael Svensson (Örebro University School of Business, 2008)
This paper studies the relationship between the business cycle and alcohol sales in Sweden using a data set for the years 1861-2000. Using wavelet based band-pass filtering it is found that there is a pro-cyclical relationship, i.e. alcohol sales increases in short-term economic upturns. Using moving window techniques we see that the pro-cyclical relationship holds over the entire time period. We also find that alcohol sales are a long-memory process with non-stationary behavior, i.e. a shock in alcohol sales has persistent effects
Keywords: E32; I12; 330; Businesscycles:Alcohol:Sweden